Оцінка декоративності дендросозоекзотів ex situ Степу України - Власенко, Анастасія; Vlasenko, Anastasia (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті проаналізовано сучасні методики оцінки декоративності деревних рослин, на основі чого розроблено оригінальну шкалу комплексної оцінки, яку апробовано на 30 видах дендросозоекзотів ex situ, що охороняються на територіях природно-заповідного фонду Степу України. The modern methodologies for assessing decorativeness of woody plants were analyzed. On this basis the original integrated scale of decorativeness assessment of rare arboreal exotic plant species by the main morphological features was constructed. This scale was optimized for leaf-losing and evergreen coniferous, as well as deciduous trees and shrubs. The resulting rating scale comprises four blocks: assessment of the general decorativeness of plants, evaluation of decorativeness of bark, assessment of decorativeness of leaves or needles, as well as the generative organs of the plant. This method was tested on 30 species of rare arboreal plants, which are protected ex situ on the territories of Nature Reserve Fund of the Steppe of Ukraine. According to the evaluation, three species of rare arboreal plants were categorized as most decorative (Malus niedzwetzkyana Dieck ex Koehne, Cercis chinensis Bunge and Liquidambar styraciflua L.), 23 species – as highly decorative species and four – as species of middling decorativeness. The results of decorativeness evaluation of rare arboreal plants ex situ of Nature Reserve Fund of the Steppe of Ukraine are support the view of the necessity of their widespread use in landscape gardening.
Evaluation of Decorativeness of Rare Arboreal plants Ex Situ of the Steppe of Ukraine
Keywords: assessment of decorativeness; Steppe of Ukraine; ex situ; rare arboreal plants; оцінка декоративності; Степ України; дендросозоекзоти